Endoscopic removal of a toothbrush in a young adult with psychiatric disorder - Alvizuri-Gómez, Claudia (2021)
Ingestion of foreign bodies is a relative common situation in the emergency department; however, ingestion of toothbrush is rarely reported in the literature. We present the case of a 27-year-old man with a previous diagnosis of obsessive-compulsive disorder, who presented to the emergency department 17 hours after an ingestion of a toothbrush. We performed an endoscopic removal using a polypectomy snare in the Gastroenterology Department under moderate sedation. No complications were reported in the procedure and the patient was discharged few hours later. Ingestion of toothbrush is rare in the literature and some authors described techniques using overtube and retractable snares and forceps. Endoscopic removal of a toothbrush under mod dure. However, if endoscopic removal fails, surgery should be performed.